“Stop perundungan, mari kita berteman!” penyuluhan dan edukasi anti perundungan untuk siswa sekolah dasar - Aurick Daffa Muhammad; Achmad Rizal; Enzel D. S. Situmorang; La Bamba Puang P T S Kami; Nurul Fathanah Muntasir; Vania Rei Syifa; Muhammad Al Makky (Institut Teknologi Dirgantara Adisutjipto, 2023)
Bullying is an unpleasant behavior carried out by an individual or a group of people against another person or group. This behavior is carried out both verbally and physically which can make a person feel uncomfortable and pressured. Bullying often occurs at the elementary school (SD) level. This happens because the elementary school age level does not understand the meaning of bullying and its legal consequences. Therefore, in this community service, counseling was carried out for Al Mabrur Elementary School students to provide an understanding of bullying. Counseling was carried out through various activities, such as playing videos, presenting material, coloring, games, and handing out anti-bullying pocket books. The counseling activity was attended by 30 students from SD Al Mabrur and other school employees. Based on the results of the questionnaire given to the participants after the counseling was finished, it was found that the participants had understood the meaning of bullying and its forms.